The effects of marine heatwaves on acute heat tolerance in corals. Issue 2 (26th October 2022) - Marzonie, Magena R.; Bay, Line K.; Bourne, David G.; Hoey, Andrew S.; Matthews, Samuel; Nielsen, Josephine J. V.; Harrison, Hugo B.
Abstract: Scleractinian coral populations are increasingly exposed to conditions above their upper thermal limits due to marine heatwaves, contributing to global declines of coral reef ecosystem health. However, historic mass bleaching events indicate there is considerable inter‐ and intra‐specific variation in thermal tolerance whereby species, individual coral colonies and populations show differential susceptibility to exposure to elevated temperatures. Despite this, we lack a clear understanding of how heat tolerance varies across large contemporary and historical environmental gradients, or the selective pressures that underpin this variation. Here we conducted standardised acute heat stress experiments to identify variation in heat tolerance among species and isolated reefs spanning a large environmental gradient across the Coral Sea Marine Park. We quantified the photochemical yield ( F v /F m ) of coral samples in three coral species, Acropora cf humilis, Pocillopora meandrina, and Pocillopora verrucosa, following exposure to four temperature treatments (local ambient temperatures, and + 3°C, +6°C and + 9°C above local maximum monthly mean). We quantified the temperature at which F v /F m decreased by 50% (termed ED50) and used derived values to directly compare acute heat tolerance across reefs and species. The ED50 for Acropora was 0.4–0.7°C lower than either Pocillopora species, with a 0.3°C difference between the two Pocillopora species. We also recorded 0.9°C to 1.9°C phenotypic variation in heat tolerance among reefs within species, indicating spatial heterogeneity in heat tolerance across broad environmental gradients. Acute heat tolerance had a strong positive relationship to mild heatwave exposure over the past 35 years (since 1986) but was negatively related to recent severe heatwaves (2016–2020). Phenotypic variation associated with mild thermal history in local environments provides supportive evidence that marine heatwaves are selecting for tolerant individuals and populations; however, this adaptive potential may be compromised by the exposure to recent severe heatwaves. Abstract : We show extensive spatial variation in heat tolerance in corals associated with a population's exposure to marine heatwaves. More frequent exposure to mild heatwaves increased heat tolerance in populations but recent severe heatwaves had a negative effect. The link between heat tolerance and marine heatwaves is evidence that corals can adapt to their local environment but that corals cannot adapt at the rate that heatwaves are occurring.